GLOBAL MARKETING AND THE DIGITAL REVOLUTION - Suhairi Suhairi; Dwi Franadita; Epa Purnama Sari; M. Adhie Husni (Bussman Journal : Indonesian Journal of Business and Management, 2023)
Global marketing and the digital revolution are growing from time to time providing convenience to every user or person who does it. With the existence of global marketing and digital revolution, this has also brought changes in integration to transactions. According to Warren J. Keegan & Mark C. Green (2017: 585), Global Marketing is the commitment of organizational resources to pursuing global market opportunities and responding to environmental threats in the global marketplace, which means the commitment of an organization's resources to pursue opportunities global markets and respond to threats in the global market environment. There is an opportunity to pursue a global market with a global market environment that is growing with the digital revolution. This study aims to find out how global marketing and the digital revolution are in the current era. This research uses qualitative methods, the data used is secondary, namely from literature books, as well as journals, related articles. Based on the results, the growing development of global marketing and the digital revolution makes it easy for companies, business people, MSME actors and others to develop products, develop ideas, seek more relevant understanding to enter the global market and improve the economy and reduce unemployment